Impact of Working Patterns on Employee Engagement With the Mediating Role of Trust (Journal of Asian Development Studies, 2024)
The objective of this study is to find out the impact of working patterns on employee engagement with the mediating role of trust in the banking industry and financial institutes of Pakistan. The data is collected through a research survey with the help of Google Forms from the different workers of banks and financial institutes in Pakistan. A quantitative approach is adopted in this particular study. The 305-sample size is collected through bank and financial institution employees. For analysis of data SMART PLS-4 is used to analyze the relationship of dependent and independent variables. Our findings suggest that workload, Job Autonomy, and work environments have successfully predicted employee engagement with the mediator of trust, and Job crafting has an insignificant impact on employee engagement. This study contributes to the organization by examining practices that employees perceive as support that leads to engagement.